Copper causes reduced nitrogen fixation but does not accumulate in the nodules of the legume Lotus japonicus - Kathryn Lamoureux; Sheila M. Macfie (PLoS ONE, 2026)
Copper can be a soil contaminant at concentrations that are toxic to plants, particularly because of copper-induced oxidative stress. The legume-rhizobia partnership that allows for biological nitrogen fixation is sensitive to oxidative stress, and this study investigates if copper acts directly on the machinery of nitrogen fixation, or indirectly via toxicity to the entire plant. When Lotus japonicus inoculated with its rhizobial partner Mesorhizobium loti was exposed to 300 or 450 µM of copper, biomass was reduced by 30–40% in the shoots, 40–55% in the roots, and 40–60% in the nodules relative to control. While concentrations of copper in shoots and roots increased in proportion to the amount of copper in the growth medium, concentrations of copper in nodules did not vary in response to copper treatment. Malondialdehyde, a marker of oxidative damage, in the nodule similarly did not vary with copper treatment. However, nitrogen fixation and ascorbate peroxidase activity decreased by 40–45% and 40–60%, respectively, which can be indicators of early nodule senescence. This would suggest that copper-induced reduction in nodule activity is not directly due to oxidative stress in the nodules; it is due to stress on the host plant that limits its ability to support its symbionts.